Improving Employee Performance through Employee Performance Assessment Mechanism at the Malang Regency Transportation Service - R.M Mahrus Ali; Ria; Sinollah (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2025)
This study analyzes the employee performance assessment system at the Malang Regency Transportation Office, based on observations and interviews with several employees. Performance assessments are carried out annually with quarterly evaluations by the head of the sub-division. Evaluations include employee performance, financial administration, and staffing. The assessment process involves several stages: Annual Work Plan (RKT), Performance Agreement, Employee Performance Targets (SKP), and the use of the "SIAP KERJA" Application. The RKT is prepared as an elaboration of the Agency's strategy and facilitates program evaluation. A Performance Agreement is a commitment document between leaders and subordinates related to the implementation of tasks with performance indicators. SKP includes targets that must be achieved in a certain period, measured based on quantity, quality, time, and cost. The results of this assessment are then summarized in the "SIAP KERJA" Application, which experiences technical problems such as frequent errors or maintenance. The suggested solution is to fill in daily activities regularly. This performance assessment aims to improve the integrity, accountability, transparency, and performance of the apparatus, as well as be the basis for evaluation, awards, and sanctions to employees.